2005
DOI: 10.1038/sj.hdy.6800654
|View full text |Cite
|
Sign up to set email alerts
|

A single locus determines thelytokous parthenogenesis of laying honeybee workers (Apis mellifera capensis)

Abstract: The evolution and maintenance of parthenogenetic species are a puzzling issue in evolutionary biology. Although the genetic mechanisms that act to restore diploidy are well studied, the underlying genes that cause the switch from sexual reproduction to parthenogenesis have not been analysed. There are several species that are polymorphic for sexual and parthenogenetic reproduction, which may have a genetic basis. We use the South African honeybee subspecies Apis mellifera capensis to analyse the genetic contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
95
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 31 publications
(39 reference statements)
5
95
0
1
Order By: Relevance
“…Contagious asexuality has been reported in a wide range of arthropods (Delmotte et al, 2001;Lattorff et al, 2005;Paland et al, 2005;Halkett et al, 2008;Sandrock and Vorburger, 2011). When studied, inheritance of obligate asexuality has been found to be mono-or oligogenic in most cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contagious asexuality has been reported in a wide range of arthropods (Delmotte et al, 2001;Lattorff et al, 2005;Paland et al, 2005;Halkett et al, 2008;Sandrock and Vorburger, 2011). When studied, inheritance of obligate asexuality has been found to be mono-or oligogenic in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…In the rotifer Brachyonus calyciflorus, OP clones are homozygous for a recessive allele op, which renders them unable to respond to the chemical signals that usually induce sexual reproduction in this species (Scheuerl et al, 2011), whereas heterozygotes and homozygotes for the wild type are CP (Stelzer et al, 2010). In insects, all-female parthenogenesis (thelytoky) has been found to be inherited as a single-locus recessive trait in two hymenopterans, the Cape honeybee Apis mellifera capensis (Lattorff et al, 2005), and a solitary aphid endoparasitoid wasp, Lysiphlebus fabarum (Sandrock and Vorburger, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In social Hymenoptera, it has been shown that thelytoky of Apis mellifera capensis workers is controlled by a single locus (Lattorff et al, 2005). Cytological analysis indicated that diploidization results from automictic parthenogenesis with central fusion, that is, the fusion of two of the four meiotic products that have a central position on the spindles and that were separated at the first meiotic division, whereas the two terminal nuclei degenerate (Verma and Ruttner, 1983;Baudry et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The mandibular gland pheromones and ovariole development covary in queenless Cape workers (Hepburn, 1992) (both probably under separate genetic control), but thelytoky itself is a Mendelian trait (Lattorff et al, 2005). Jordan et al (2008) measured spermatheca size and number of ovarioles in the parental, hybrid and backcross offspring between thelytokous Cape bees and the highland bee A. m. scutellata and observed that they were phenotypically correlated but apparently under independent genetic control.…”
Section: Introductionmentioning
confidence: 99%